2012
DOI: 10.3892/ijmm.2012.913
|View full text |Cite
|
Sign up to set email alerts
|

Expression of thymosin β4 in odontoblasts during mouse tooth development

Abstract: Abstract. Thymosin β4 (Tβ4) is expressed in developing tissue, where it stimulates cell differentiation and migration. Further, Tβ4 is expressed during molar development in mice, but the expression and function of Tβ4 in odontoblasts during mammalian tooth development have not yet been reported. Therefore, this study examined the expression and function of Tβ4 in differentiating odontoblasts during tooth development. As observed by immunohistochemistry, Tβ4 was expressed in the oral epithelium and inside cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
1
3
1
Order By: Relevance
“…This result differs from that in a study on MDPC-23 cells [13], which showed that Tβ4 mRNA and protein was strongly increased after 4 days and decreased from 14 to 28 days during differentiation of MDPC-23 cells, which might be related to differences in cell types or species and culture conditions.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This result differs from that in a study on MDPC-23 cells [13], which showed that Tβ4 mRNA and protein was strongly increased after 4 days and decreased from 14 to 28 days during differentiation of MDPC-23 cells, which might be related to differences in cell types or species and culture conditions.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results indicate that inhibition of Tβ4 by siRNA in HDPCs decreased ALP activity, mineralized nodule formation, and upregulated the expression of mRNAs encoding odontoblastic markers, including ON, OPN, OCN, DSPP, and DMP1. These results are consistent with previous data obtained using the odontoblast-like cells MDPC-23 [13]. Furthermore, activation of Tβ4 by exogenously added Tβ4 peptide in HDPCs increased OM-induced odontoblastic differentiation in a dose-dependent manner.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Exogenous β4 peptide inhibited osteogenic differentiation but facilitated adipogenic differentiation in human bone marrow-derived-mesenchymal stem cells (MSCs) [ 16 ]. In contrast, Tβ4 inhibition by Tβ4 siRNA attenuated odontoblastic differentiation in the odontoblast-like cells, MDPC-23 [ 17 ]. Moreover, we recently demonstrated that odontoblastic differentiation was enhanced by activation of Tβ4 by Tβ4 peptide but was decreased by Tβ4 siRNA in human dental pulp cells (HDPCs) [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sooam researchers have also created new models for diabetes by putting genes that cause symptoms of the disease in mice into cloned pigs 6 and dogs 7 . Likewise, says Insung Hwang, a transgenic beagle at Sooam that carries a gene related to Alzheimer's disease shows hallmarks of the disease.…”
mentioning
confidence: 99%